Emerging ingredients for clean label products and food safety - Elizabeth Harumi Nabeshima; Paulo Eduardo da Rocha Tavares; Ana Lúcia da Silva Corrêa Lemos; Sílvia Cristina Sobottka Rolim de Moura (Brazilian Journal of Food Technology)
Abstract Emerging markets comprise different healthy food products, such as functional foods including grains, fruits, and vegetables; foods for people with dietary restrictions; foods with clean labels, plant-based and organic ingredients, as well as ingredient options to replace sodium, sugars, fats, as well as alternatives to synthetic nitrite. The variety of ingredients with potential applications in these products raises relevant safety issues due to the lack of studies about possible biological contaminants, and nutritional, chemical, microbiological and allergen concerns. Besides, certain ingredients may present the potential for allergenicity, intolerance, or other immunological reactions, such as celiac disease. Derivatives of alternative plant-based proteins are examples of these risks and should be assessed for their allergenic potential and specific microbial load. Food safety refers to risk management, based on control measures established throughout the production chain, not limited to quality tests on the final product. This review addresses the main categories of food recognized as healthy by consumers, from a food safety point of view, pointing out the potential risks and management alternatives available for this new market of clean label products.